Student errors: how teachers diagnose and respond to them - Seifried, Jürgen [Verfasser]; Wuttke, Eveline [Verfasser] (My University, 2010)
"Current pedagogical discourse has established that teacher competence is a conditio sine qua non for high level performance in the classroom. Nevertheless questions of conceptualising and measuring teacher competence have yet to be answered. In our study we analyse a facet of teacher competence essential to successful learning processes; namely, teacher competence when diagnosing and responding to student errors in a constructive manner. Two pilot studies investigate how students perceive 'error culture' in their classrooms, and how teachers deal with learner errors during lessons." (Autorenreferat, BIBB-Doku)
Keywords: L 2 Lehr-Lerngestaltung; L 3 Lehr-Lern-Forschung; P 3.2.3 Lehrer; Lehr-Lern-Forschung; Lehr-Lern-Prozess; Lehrer; Fehlerkultur; Lernarrangement